Influence of Heating on Thermal Stability of Essential Oils During Storage - Dedebas, Tugba; Ekici, Lutfiye; Sagdic, Osman (TAYLOR & FRANCIS LTD, 2022)
Volatile oils are natural products with high antioxidant activity but their chemical composition and antioxidant activities may change due to the thermal storage conditions. In the present study, the changes in antioxidant activity and thermal stability of bay laurel, lemon peel, and orange peel essential oils stored at refrigerator temperature (4 degrees C), room temperature (20 degrees C), and elevated temperature (37 degrees C) for 12 months were examined. In the determination of antiradical activity measured using DPPH method at the beginning of storage, the bay laurel essential oil (82.82%) showed a better inhibition percentage when compared to lemon (32.30%) and orange (46.52%) peel oils. During the storage, a decrease was observed in the antioxidant and antiradical activity values of the oils. The aromatic compositions of volatile oils were determined using GC/MS and the main components of volatile oils were found to be 1,8 Cineolene (50.4%) for bay laurel, d-limonene (80.1%) for lemon peel, and d-limonene (94.6%) for orange peel. At the end of this study, it was found that the change in the compositions of essential oil samples stored in the refrigerator was at a lower level, whereas significant changes were observed in both volatile compositions and antioxidant activity values of the samples stored at elevated temperatures. Moreover, it was also observed that the volatile oils obtained might form natural potential agents that can be used as antioxidant in food products.
Keywords: Essential oils; Oxidative stability; Aroma; Storage; LAURUS-NOBILIS L.; CHEMICAL-COMPOSITION; ANTIOXIDANT ACTIVITY; LEAVES; ANTIBACTERIAL; Plant Sciences